Implikasi Isbath Nikah Terhadap Status Istri, Anak Dan Harta Dalam Perkawinan Dibawah Tangan - Muhammad Andri (Jurnal Penegakan Hukum Indonesia, 2020)
Law Number 1 of 1974 article 2 paragraph (2) clearly mandates the registration of marriages, but the fact is that in the community there are still marriages that are not recorded, this is evidenced by the existence of marriage ceremoniesin Indonesia such as in the high court of the East Java religion, which has granted the case. petition (voluntary) for 679 cases that were granted according to the performance report of the High Religious Court in 2019. The problem raised is how the implications of marriage isbath on the status of wife, children and marital assets in an underhand marriage. The research method in writing this article is a normative legal research method, which is research that is focused on examining the application of the norms or norms in positive law. Normative legal research methods are usually qualitative (not in the form of numbers).In his findings that the implication of marriage isbath on the status of wife, children and marital assets in an underhand marriage, that the existence of a marriage certificate in accordance with Supreme Court Regulation No.1 of 2015 has legal consequences if an application is made for legalization of marriage which implies legal guarantees of husband and wife marital relations , children and birth certificates, assets in marriage can obtain legal guarantees.